2019
DOI: 10.1115/1.4042184
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Order Models for Transstenotic Pressure Drop in the Coronary Arteries

Abstract: The efficacy of reduced order modeling for transstenotic pressure drop in the coronary arteries is presented. Coronary artery disease is a leading cause of death worldwide and the computation of pressure drop in the coronary arteries has become a standard for evaluating the functional significance of a coronary stenosis. Comprehensive models typically employ three-dimensional (3D) computational fluid dynamics (CFD) to simulate coronary blood flow in order to compute transstenotic pressure drop at the arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…In particular, reduced order modeling seems to be the most appropriate strategy, as it is a reasonable balance between the suitable level of local detail and the overall response (see, among the most recent [19][20][21][22][23] ). Multiscale modeling has already provided useful insights into aging 24,25 , coronary pathologies 26,27 , and cardiac arrhythmias [28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, reduced order modeling seems to be the most appropriate strategy, as it is a reasonable balance between the suitable level of local detail and the overall response (see, among the most recent [19][20][21][22][23] ). Multiscale modeling has already provided useful insights into aging 24,25 , coronary pathologies 26,27 , and cardiac arrhythmias [28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…In the field of cardiovascular disease treatment, the fact that myocardial tissue lacks self-repairing ability is a serious challenge [ 46 ]. Traditional treatments, such as pharmacological therapy, angioplasty, and coronary artery bypass surgery, cannot restore necrotic and fibrotic damaged myocardium to the normal state [ 47 , 48 ]. In recent years, it has been found that stem cell transplantation can repair diseased myocardium [ 49 ].…”
Section: 3d Bioprinting Of Ipscs In Tissue Engineeringmentioning
confidence: 99%
“…We use the same elastic pressure law (3) to couple the flow and the wall. This model has been previously used in the literature [12,17,18,23] to compute the flow in the systemic circulation to study the presence of a stenosis.…”
Section: One-dimensional Modelmentioning
confidence: 99%
“…Complex models for blood flow are based on the Navier-Stokes equations [8,18]. Solving the fluid flow coupled to the displacement of the arterial wall in a three-dimensional (3D) domain is complex and requires high computational resources.…”
Section: Introductionmentioning
confidence: 99%